Textual Research on the Uprising of the Taiping Heavenly Kingdom: The Change of the Name of the Taiping Heavenly Kingdom (Asian Journal of Social Science Studies, 2022)
The study of the Taiping Kingdom itself has a great influence on the study of the history of the Taiping Kingdom in modern China. It involves the research of politics, economy, culture, military, figures, laws and regulations, religion and so on. However, the academic research on the national title of the Taiping Heavenly Kingdom is less involved. Investigating this history will not only help us understand the historical details of the Taiping Heavenly Kingdom period, but also correct some wrong understandings about the name of the Taiping Heavenly Kingdom.